The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/hr.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities and home blood pressure in treated elderly hypertensive patients: Japan home versus office blood pressure measurement evaluation in the elderly (J-HOME-Elderly) study

Abstract: , and the J-HOME-Elderly study group 6This study compares relationships between each of morning home blood pressure (BP), evening home BP and office BP with electrocardiographic (ECG) abnormalities among treated hypertensive Japanese patients. We defined ECG left ventricular hypertrophy (LVH) as Sokolow-Lyon voltage and/or Cornell voltage duration product. Abnormal T waves and ST segment depression were categorized based on the Minnesota code. Office BP was calculated as the mean of four readings taken during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Target organ damage could still be observed in patients with morning hypertension who received antihypertensive therapy [ 28 ]. Shibamiya et al found that the risk of LVH increased by 23% for every 10 mmHg increase in morning systolic blood pressure [ 29 ]. The results of this study also demonstrated that inadequate morning blood pressure control was the main reason for the increased risk of LVH in postmenopausal hypertension patients.…”
Section: Discussionmentioning
confidence: 99%
“…Target organ damage could still be observed in patients with morning hypertension who received antihypertensive therapy [ 28 ]. Shibamiya et al found that the risk of LVH increased by 23% for every 10 mmHg increase in morning systolic blood pressure [ 29 ]. The results of this study also demonstrated that inadequate morning blood pressure control was the main reason for the increased risk of LVH in postmenopausal hypertension patients.…”
Section: Discussionmentioning
confidence: 99%
“…[120][121][122] Those who exhibit large morning-evening differences in BP have marked target organ damage, such as left ventricular hypertrophy. [123][124][125][126] However, home BP measured in the evening also has a high prognostic significance. 117,127 In contrast, there have been a number of reports from Western countries that home BP does not differ between the morning and evening, or that home BP is higher in the evening than in the morning.…”
Section: Masked Hypertensionmentioning
confidence: 99%
“…The incidence of left ventricular hypertrophy (LVH), as identified by electrocardiogram, was lower with strictly controlled home BP was compared with routine home BP control. Furthermore, elevated home BP is more strongly associated with an increase in LV muscle mass, and the presence of LVH compared to elevated office BP [ 2 , 3 ]. In particular, morning home BP is more closely associated with LVH compared to office BP or evening home BP [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated home BP is more strongly associated with an increase in LV muscle mass, and the presence of LVH compared to elevated office BP [ 2 , 3 ]. In particular, morning home BP is more closely associated with LVH compared to office BP or evening home BP [ 2 ]. Proteinuria and carotid artery intima-media thickness (IMT) is more closely correlated with home BP than office BP [ 4 , 5 ], and the carotid artery IMT is more closely correlated with systolic home BP than systolic office BP (0.34 vs. 0.25, P < 0.001) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation